PENGARUH MODEL DISCOVERY LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK KELAS VIII SMPN 2 SAWAHLUNTO - Oktaviani, Tasya Putri (Jurnal Edukasi dan Penelitian Matematika, 2024)
Critical thinking is crucial. The SMPN 2 Sawahlunto observations demonstrated this skill is still absent. Our study evaluated how Discovery Learning (DL) can develop this skill. SMPN 2 Sawahlunto Class VIII was the study population. Simple random sampling yielded class VIII 3 as the control and VIII 4 as the experimental. WE adopted Non-Equivalent Posttest Only Control Group Design. The results indicate that if the P-value is below the significance level (?), adopt the alternative hypothesis (H1). Evidence suggests the DL model increases critical thinking.